Glomus tumor: an atypical presentation - K. A., Rajeshwari; R., Rajagopal (International Journal of Research in Dermatology, 2020)
Glomus tumors are rare soft-tissue neoplasms of the neuromyoarterial glomus body, typically present in adults as small, blue-red papules or nodules of the distal extremities, with most cases involving subungual sites. The majority of glomus tumors are benign, malignant cases have been rarely reported, with such cases typically being locally invasive. 27 years old patient presented with four years history of intermittent swelling, pain in left lower leg. Biopsy of the lesion revealed lobulated vascular tumour composed of endothelial cells showing intracytoplasmic lumina and solid aggregates of tumour cells, divided by intervening fibrocollagenous septae. Glomus tumour of uncertain malignant potential was diagnosed after excision biopsy. Multispeciality team approach was done for complete cure of the condition.